Redox Regulation of Protein Function via Cysteine S-Nitrosylation and Its Relevance to Neurodegenerative Diseases - Mohd Waseem Akhtar; Carmen R. Sunico; Tomohiro Nakamura; Stuart A. Lipton (International Journal of Cell Biology)
Debilitating neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD), can be attributed to neuronal cell damage in specific brain regions. An important hallmark of these diseases is increased oxidative and nitrosative stress that occurs via overproduction of highly reactive free radicals known as reactive oxygen species (ROS) and reactive nitrogen species (RNS). These molecules are normally removed by cellular antioxidant systems. Under physiological conditions, ROS/RNS are present at low levels, mediating several neurotrophic and neuroprotective signaling pathways. In contrast, under pathological conditions, there is a pronounced increase in ROS/RNS generation, impairing normal neurological function. Nitric oxide (NO) is one such molecule that functions as a signaling agent under physiological conditions but causes nitrosative stress under pathological conditions due to its enhanced production. As first reported by our group and colleagues, the toxic effects of NO can be in part attributed to thiol S-nitrosylation, a posttranslational modification of cysteine residues on specific proteins. Here, we review several reports appearing over the past decade showing that S-nitrosylation of an increasing number of proteins compromises important cellular functions, including mitochondrial dynamics, endoplasmic reticulum (ER) protein folding, and signal transduction, thereby promoting synaptic damage, cell death, and neurodegeneration.